2013
DOI: 10.1038/aja.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment strategies for older prostate cancer patients with bone metastasis

Abstract: To identify the clinical features and independent predictors of survival in older patients with bone metastasis from prostate cancer (PCa). We retrospectively analysed 205 older patients with bone metastases from PCa between 1997 and 2012. The Kaplan-Meier method was used with the log-rank test for survival rate calculations and to evaluate each variable. Multivariate analysis was performed with the Cox regression model. The chi-squared test was used to compare survival rates between older and younger (n5197) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…However, it was observed that older patients with prostate cancer had higher survival durations. This finding is supported by the results of the study carried out by Yang et al (2013) who reported that older patients with single-bone metastasis had a higher survival rate 18 . It was also seen that there was a significant difference between prostate cancer patients with tumors of different stages in terms of their overall survival time (p>0.001), such that patients with tumors stages I had the longest survival duration, followed by those with stages II and II.…”
Section: Discussionsupporting
confidence: 52%
“…However, it was observed that older patients with prostate cancer had higher survival durations. This finding is supported by the results of the study carried out by Yang et al (2013) who reported that older patients with single-bone metastasis had a higher survival rate 18 . It was also seen that there was a significant difference between prostate cancer patients with tumors of different stages in terms of their overall survival time (p>0.001), such that patients with tumors stages I had the longest survival duration, followed by those with stages II and II.…”
Section: Discussionsupporting
confidence: 52%
“…The Gleason scoring system is a well-established predictor for staging, progression and prognosis in PCa 14. Yang et al 15 reported that Gleason score was associated with survival of PCa patients with bone metastasis. The overall survival of patients with Gleason score ≤7 was significantly longer than in patients with score >7.…”
Section: Discussionmentioning
confidence: 99%
“…PCa frequently metastasizes to bone, and studies have shown that bone metastases (BMs) have occurred in 13.3%-26% of PCa patients at the first diagnosis in China, which is far more than the rates of 3%-10% in European countries and 3%-5% in the United States 6-8. Once BM occurs in a PCa patient, treatment is very limited and the survival rate is greatly reduced 9. Currently, the technetium Tc 99m methylene diphosphonate (Tc 99m MDP) bone scan method is accepted as the standard and is the most frequently used examination to diagnosis bone metastasis in PCa 10.…”
Section: Introductionmentioning
confidence: 99%